Early postoperative PTH level following total thyroidectomy as a predictor of hypocalcemia: a single center-based study in Bangladesh - Hoque, Emdadul; Hamid, Kawser; Sakil, Riaz Ahmed; Bhuiyan, Haroun or Rashid (Central Medical College Journal, 2023)
Background: Assessment of parathyroid hormone (PTH) following thyroid surgery assists in the prediction of hypocalcemia and permits early intervention and therapy with oral calcium and/or vitamin D supplements. Methods: This retrospective analysis comprised 141 individuals who had undergone a total or completion thyroidectomy over the previous four years. The blood PTH level was measured 3 hours after surgery to determine its change and to predict hypocalcemia. Results: Patients were predominately female (75.2%), and the mean age was 48.73 ± 13.44 years. The main surgical procedure was total thyroidectomy (80.14%), and the main cause for surgery was a multinodular goiter (34.04%). A comparable number of patients with each type of thyroid disease (multinodular goiter, papillary thyroid cancer, thyroiditis, Graves’ disease or toxic multinodular goiter were enrolled. Three hours after surgery 93 patients (65.95%) had serum PTH levels of >10 pg/ml (mean 28.06) and 90 patients (68.38%) had normal serum calcium (mean 8.66). Most of these 93 patients (65.95%) didn't require postoperative supplementation, whereas 48 patients (34.05 %) with serum PTH levels less than 10 pg/ml required some form of supplementation; 39 (27.65 %) required both oral calcium and vitamin D supplements, and 9 (6.4 %) required only oral vitamin D supplementation. There was a significant correlation between the 3-h postoperative PTH level and hypocalcemia (P-value 0.000). The type of pathology had no significant association with low serum PTH level after surgery (P-value 0.166). Conclusion: Asymptotic individuals with PTH levels less than 10 pg/ml, who are regarded as being in the high-risk category, can start taking calcium and/or vitamin D supplements early if their PTH levels are measured at 3 hours following complete thyroidectomy. To predict hypocalcemia, more research is required to compare the outcome of early serum PTH level with the day one serum PTH level following complete thyroidectomy. Central Medical College Journal Vol 6 No 2 Jauly 2022 Page: 82-89